Development of indium zinc oxide coated kenaf reinforced PANi/PLA composite for electromagnetic interference shielding - Abdullah Sani, Nurhernida (2024)
Electromagnetic interference (EMI) has emerged as a major concern for disrupting the performance or operation of electrical equipment as well as being harmful to human health. In order to cope with the interference issues, an innovative development of biodegradable polymer blends incorporating intrinsic conductive polymers (ICPs) such as polyaniline (PANi) was pursued for EMI shielding applications. Nevertheless, PANi-filled polymer blends are frequently susceptible to weakening the mechanical properties due to agglomeration and weak adhesion issues. Thus, the research aims to improve the mechanical properties as well as the electrical properties of PLA/PANi polymer blends by reinforcing them with indium doped zinc oxide (IZO) coated kenaf fiber. In Stage 1, the development of conductive IZO coated kenaf fiber was performed via dip coating process and systematic statistical approach to obtain the most suitable level of alkaline treatment, annealing temperature and indium doping, in order to achieve the lowest surface resistivity possible, indicating an increase in charge carrier. It was found that the combination of an annealing temperature of 130 °C, NaOH treatment of 8.0 % and indium doping of 3.0 wt% has yielded a minimal surface resistivity of 1.87 x 109 Ω/sq with the highest desirability value of 0.933. In addition, the characterizations via XRD, FTIR, morphological and elemental analysis have validated the succesful coating of the IZO on kenaf fiber. In the following Stage 2, the fabrication of biodegradable PLA/PANi polymer blends has been performed to study their electrical, thermal and EMI shielding effectiveness (EMISE) performance. Prior to that, PANi were synthesised via chemical oxidative polymerization (COP) with hydrochloric acid doping. Then, PANi was incorporated into the PLA to produce conductive polymer blends via a melt-mixing process, which were then hot-pressed into polymer sheets. The increasing amount of PANi in the polymer blends has increased the electrical conductivity and the dielectric properties; however, it has substantially reduced the mechanical properties and the thermal stability. In the final Stage 3, the development of the IZO-kenaf/PANi/PLA hybrid composite was carried out using hot compression molding. In this process, the combination of PANi amount (per-hundred-resin) and IZO-coated kenaf fiber weight percentage (wt.%) were investigated using a two-level full factorial statistical approach method to achieve the highest mechanical, electrical and EMISE performance resulting from the synergistic integration of the IZO-kenaf/PANi/PLA hybrid composite. The most suitable compositions of IZO-kenaf and PANi were determined to be 30 wt.% and 10 phr, respectively. The most suitable quantity of IZO-kenaf and PANi was successfully combined, resulting in the highest EMI shielding efficacy value of 42.6 dB, conductivity of 2.39 x 10-4 S/m, and permittivity value of 6.60. The highest incorporation amount of IZO-kenaf has raised the tensile strength and modulus to 16.6 MPa and 4.04 GPa, respectively, which indicates the reinforcing effect of IZO-coated kenaf fiber. As a result, the synergistic effects from the integration of IZO-coated kenaf fiber and PANi/PLA matrix has improved the electrical, mechanical and EMISE properties, making it a potetial alternative for EMI shielding applications.